Overview and comparison of Besshi-type deposits ancient and recent - Schoeman, Philo (Rhodes University, Faculty of Science, Department of Geology, 1996)
Besshi-type deposits range in age from early Proterozoic to early Tertiary, of which the largest number are late Proterozoic, early Palaeozoic or Mesozoic in age. No Archaean examples of Besshi-type deposits are known, probably due to insufficient availability of sialic crust for erosion and clastic marine sedimentation before the start of the Proterozoic. All Besshi-type deposits are contained within sequences of clastic sedimentary rock and intercalated basalts in a marine environment. The basalts and amphibolites are principally tholeiitic in composition. Besshi-type deposits characteristically form stratiform 1enses and sheet-like accumulations of semi-massive to massive sulphide. The main ore assemblage consists dominantly of pyrite and/or pyrrhotite with variable amounts of chalcopyrite, sphalerite and trace galena, arsenopyrite, gold and e1ectrum, barite being absent in general. The median Besshi-type deposit (n=75) contains 1.3 million tonnes (Mt) of massive sulphide with a Cu grade running at 1.43%. It is suggested that Besshi-type deposits form by both exhalative and synsedimentary replacement processes when considering geological features and comparisons with modern analogues in the Guaymas Basin, Middle Valley and Escanaba Trough. The currently forming metalliferous sediments in the Red Sea provide for a brine pool model explaining the lack of footwall feeder zones below sheet-like deposits. Where thick sulphide lenses are contained in some Besshi-type deposits, combinations of exhalative precipitation and sub-sea-floor replacement of permeable sediments and/or volcanic rocks, take place in the upper parts of submarine hydrothermal systems.
Keywords: Ore deposits -- Japan; Ore deposits -- Canada; Ore deposits -- Namibia; Ore deposits -- South Africa; Ore deposits